A YAP1:TFE3 cutaneous low‐grade fibromyxoid neoplasm: A novel entity!. Issue 4 (14th December 2021) - Patton, Ashley; Bridge, Julia A.; Liebner, David; Chung, Catherine; Iwenofu, O. Hans
Abstract: Cutaneous fibromyxoid neoplasms (CFMN) comprise a vast category of benign and malignant tumors that include, but are not limited to, low‐grade fibromyxoid sarcoma, myxofibrosarcoma, myxoid dermatofibrosarcoma protuberans, myxoid solitary fibrous tumor, and myxoid neurofibroma with differing implications for treatment and prognosis. Herein, a case of CFMN arising as a painless, slow‐growing, flesh‐colored forearm mass in a 53‐year‐old female is presented. The neoplasm comprised of copious myxoid material with banal spindle cells, exhibiting mild hyperchromasia, dissecting the dermal collagen table. Focal perivascular accentuation of spindle cells was identified in the absence of vasoformative features. Immunohistochemically, lesional cells were strongly and diffusely positive for CD34 and multifocally for Factor XIIIa and epithelial membrane antigen while negative for CD31, ERG, FLI‐1, D2‐40, smooth muscle actin, Desmin, S100, HMB‐45, STAT6, MUC4, and keratins. RNA‐ and DNA‐sequencing identified a YAP1::TFE3 fusion transcript that were subsequently corroborated by fluorescence in situ hybridization and immunohistochemistry for TFE3 (Xp11.23) locus rearrangement and strong, diffuse TFE3 immunoreactivity, respectively. To date, the YAP1::TFE3 fusion has only been identified in a subset of epithelioid hemangioendotheliomas and clear cell stromal tumors of the lung. This is the first report of a CFMN featuring a YAP1::TFE3 fusion ( YAP1 Exon 1 and TFE3 Exon 4). The morphologic findings are unlike those previously described for epithelioid hemangioendothelioma and suggest that this neoplasm may represent a yet unclassified or novel CFMN entity. Although the patient is 1‐year status postsurgical excision with no evidence of clinical recurrence, the clinical behavior of this novel entity remains to be fully characterized.